The Optimal Treatment of Thyroid Gland Function Disturbances During Pregnancy - Drews, Krzysztof; Seremak-Mrozikiewicz, Agnieszka (Current Pharmaceutical Biotechnology, 2011)
Thyroid disorders are quite a common health problem in pregnant women, thus adequate treatment in this period is very important in order to decrease maternal and fetal morbidity. The prevalence of hyperthyroidism is estimated to be present in approximately 0.2-0.4% of all pregnancies and the most common is Graves disease. Untreated hyperthyroidism is connected with disturbed fertilisation, recurrent miscarriages, preeclampsia development, hypotrophy of the fetus, and haemorrhage in the postpartum period. Hypothyroidism is found in pregnant women in 0.3-0.7% of all cases. Uncontrolled hypothyroidism in pregnancy can lead to preterm birth, low birth weight and mental retardation. The goal of the treatment of both hypo- and hyperthyroidism is to reach a stable euthyroid state by applying thyroid hormones or antithyroid drugs, respectively. It seems that well-controlled management of thyroid diseases does not pose any problem for pregnancy. However, the most important is to avoid any neurological abnormalities in the fetus in hyperthyroid women resulting from antithyroid drugs exposure. Moreover, it is also crucial to abstain from subclinical hypothyroidism and hypothyroxinaemia in the mother and its effect on the fetus's development which merits exact screening and intense monitoring. In this paper we described the complex pharmacology of the drugs that are used in pregnant women suffering from thyroid disorders, considering the clinical application, practical recommendation, and side effects in pregnancy and lactation. This systematic analysis could contribute some pharmacological knowledge which will be helpful in the clinical management of thyroid disorders during pregnancy.
Keywords: disturbed fertilisation